Molecular characterization of a phytoplasma of the ash yellows group (16Sr VII-B) occurring in Artemisia annua and Conyza bonariensis weeds - Meneguzzi, N.G.=700 1 Torres, L.E.; Galdeano, E.; Guzman, F.A.; Nome, S.F.; Conci, L.R.
(Es, En)
ilus., 32 ref.
Keywords: FITOPLASMAS; ORGANISMOS PATOGENOS; DISTRIBUCION GEOGRAFICA; ARGENTINA; AGRISCENTIA